Atmospheric HCFC-22 total columns near St. Petersburg: stabilization with start of a decrease. Issue 11 (2nd June 2020) - Polyakov, Alexander; Virolainen, Yana; Poberovskiy, Anatoliy; Makarova, Maria; Timofeyev, Yuriy
ABSTRACT: We study the changes in the growth rate of atmospheric HCFC-22 (CHClF2, or chlorodifluoromethane) total column (TC) in the vicinity of St. Petersburg, Russia (60° N). Although HCFC-22 surface concentrations at the two nearest sites of the Halocarbons and other Atmospheric Trace Species group (HATS) (53.3° N and 71.3° N) and mean HCFC-22 mixing ratios in the upper troposphere measured by the Atmospheric Chemistry Experiment Fourier Transform Spectrometer (ACE FTS) in the latitude range of 55‒65° N continue to increase, their growth rate is slowing down, especially in the last three years. Analysis of the temporal variability of HCFC-22 TCs measured at the St. Petersburg site of Network for the Detection of Atmospheric Composition Change (NDACC) shows that its total atmospheric abundancy reached a maximum in 2016‒2017 and is currently decreasing. Thus, the measurements in the atmosphere above St. Petersburg have detected a local decrease of the HCFC-22 content, which demonstrates the effectiveness of restrictions on the production of HCFC-22.